Nutritional, phytochemical and pharmacological properties of Mikania micrantha Kunth - Ishak, Amirah Haziyah; Shafie, Nurul Husna; Mohd Esa, Norhaizan; Bahari, Hasnah (Universiti Putra Malaysia Press, 2016)
Mikania micrantha Kunth (Asteraceae) is a perennial creeping vine that can be found in South and North America, Africa, Pacific Islands and Southeast Asia, including Southern China and Malaysia. Previous studies have reported that this plant possesses several pharmacological properties which can be used to prevent and cure several diseases. Phytochemicals found from various parts of M. micrantha have been linked to beneficial medicinal properties such as antioxidant, antimicrobial, antitumour, anti-inflammatory, anti-stress, and also anti-diabetic activities. The primary aim of this paper is to review available scientific information on the nutritional, phytochemical and pharmacological properties of M. micrantha to provide baseline information for future studies.